2021
DOI: 10.1038/s41408-021-00581-6
|View full text |Cite
|
Sign up to set email alerts
|

JAK2V617F variant allele frequency >50% identifies patients with polycythemia vera at high risk for venous thrombosis

Abstract: Arterial (AT) and venous (VT) thrombotic events are the most common complications in patients with polycythemia vera (PV) and are the leading causes of morbidity and mortality. In this regard, the impact of JAK2V617F variant allele frequency (VAF) is still debated. The purpose of the current study was to analyze the impact of JAK2V617F VAF in the context of other established risk factors for thrombosis in a total of 865 2016 WHO-defined PV patients utilizing two independent cohorts: University of Florence (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 32 publications
3
50
2
Order By: Relevance
“…It will be interesting to investigate the relationship between NLR values and the allelic burden of JAK2 V617F, which has recently been reported to be correlated with venous thrombosis [ 24 ]. Furthermore, it is worth noting that the association of absolute values of circulating neutrophil, lymphocyte, and monocyte with venous but not with arterial thrombosis was also found in essential thrombocythemia, further corroborating the role of inflammation in thrombogenesis of MPN.…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to investigate the relationship between NLR values and the allelic burden of JAK2 V617F, which has recently been reported to be correlated with venous thrombosis [ 24 ]. Furthermore, it is worth noting that the association of absolute values of circulating neutrophil, lymphocyte, and monocyte with venous but not with arterial thrombosis was also found in essential thrombocythemia, further corroborating the role of inflammation in thrombogenesis of MPN.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 , 22 Additionally, in polycythemia vera (in which JAK2 mutation accounts for >95% of driver mutations), increased JAK2 V617F burden of mutant leukocytes in peripheral blood (the variant allele frequency) is associated with increased venous thrombosis but not arterial thrombosis ( Table 1 ). 23 …”
Section: Influence Of Driver Mutations and Chip-associated Mutations ...mentioning
confidence: 99%
“…10,12 In contrast to Zhang et al who reported JAK2 V617F variant allele frequency !50% to be one of the independent risk factors affecting arterial thrombosis but not venous thrombosis, 12 Guglielmelli et al reported JAK2 V617F variant allele frequency !50% to be an independent risk factor for venous thrombosis (hazard ratio 4.0, p < 0.001) but not for arterial thrombosis (hazard ratio 0.9, p ¼ 0.8). 13 Meanwhile, the calreticulin (CALR) mutation, particularly the type 2-like CALR mutation, carries a more indolent course with fewer thrombotic events compared with JAK2 V617F and MPLmutated patients. 14,15 The International Prognostic Score for Thrombosis in ET (IPSET) has been validated to help clinicians estimate the probability of thrombotic events in ET and more recently pre-PMF.…”
Section: Mechanisms Of Thrombosis In Myeloproliferative Neoplasms And...mentioning
confidence: 99%